Solitary Wave Solutions for the Sawada-Kotera Equation - İnç, Mustafa; Kilic, Bulent; Karatas, Esra; Akgul, Ali (Amer Scientific Publishers, 2017)
In this paper, the solitary ansatz approach and the Hirota bilinear method are used to construct soliton solutions for the Sawada-Kotera equation (SKe). Topological, non-topological and multi-soliton solutions of the SKe are obtained. It is obtained the amplitude, the inverse width and the velocity of the soliton solutions. We plot two and three dimensional figures of the obtained some solutions by using Mathematica 9.
Keywords: Ansatz Approach; Hirota Bilinear Method; Sawada-Kotera Equation; Topological and Non-Topological Solitons